PEMBELAJARAN KONSEP SISTEM TATA SURYA MELALUI REASONING AND PROBLEM SOLVING BERBANTU INQUIRY TRAINING UNTUK MEMFASILITASI BERPIKIR KRITIS SISWA SD - Totok Prasetyo; Fenny Roshayanti; Sumarno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
The purpose of this study was to find out that learning using RPP and LKPD learning tools with the Reasoning and Problem Solving model assisted by Inquiry Training can facilitate students' critical thinking skills in science lesson The Solar System Concept. The method used at the development stage is the one group pretest-posttest design experimental method. The use of pretest - posttest meant that there were differences in pretest and posttest scores due to the facilitation of critical thinking skills during the learning process. The sample in this study was class VI at SD Negeri Kaliboyo 01, Tulis District, Batang Regency, with a total of 30 students. The test instrument used is a critical thinking test to determine the critical thinking skills that have been tested. The collected data were analyzed using parametric statistical analysis Paired Sample T test – test. There is an average difference between pretest and posttest learning outcomes, which means that the use of lesson plans and LKPD models of Reasoning and Problem Solving assisted by Inquiry Training improves students' critical thinking skills. From the explanation above, the Reasoning and Problem Solving learning model assisted by Inquiry Training can facilitate students' critical thinking skills.